Psychological loneliness and its relationship with depression among children with Asperger’s disorder in Riyadh, Saudi Arabia - Sultan Mousa Al-Owidha, PhD; Nevien Mohamed Zahran, PhD (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The study aimed to evaluate the relationship between psychological isolation and depression in children with Asperger syndrome and healthy children. Asperger's syndrome is a later-onset form of autism. The most distinguishing symptom of a youngster with Asperger's syndrome is a marked deficiency in social skills. The study comprised one hundred twenty-eight elementary school-aged children with and without Asperger syndrome. Children with Asperger syndrome or autism, as well as those with intellectual disability, hyperactivity, and dispersion, can benefit tremendously from early detection and early intervention measures, according to this study. The outcomes of this study are original in the academic literature since a new conceptual framework has been proposed. Moreover, the findings of this study contribute significantly to our understanding of psychological isolation. The practical consequences of this study are suitable for enhancing children's living standards by eliminating the negative aspects of their lives. In addition, the limits of the research findings stem from the research design, and this study also indicates prospects.